Artifacts in metallography: threads and fibers - A. G. Anisovich; M. I. Markevich (Литьë и металлургия)
Threads and fibers of different origin are considered as artifacts of sample preparation of metallographic sections, as well as samples of some materials. The role of various methods of optical contrasting – dark‑field illumination, polarized light – in the analysis of paper, natural and artificial fibers is illustrated. The presented materials can be used by materials scientists to identify errors in sample preparation, as well as to describe non‑traditional metallographic objects.